Pemberantasan Korupsi di Indonesia ‎(Pengembangan Wacana Keagamaan Anti Korupsi di ‎Kalangan Muhammadiyah)‎ - Sam'un Sam'un (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
Corruption has become culture in Indonesia. I is so deeply rooted in all sectors that it is difficult to be eradicated. The statistics show that Indonesia is the most corrupted country in Asia and is the fourth corrupted countries worldwide. Corruption is so dangerous that it disturbs and ruins economy and national stability, impedes development processes, and degrades morality. It also reduces trust of society as well as international community towards government so that investors and big business are discouraged to invest their money in Indonesia. Therefore, sincere efforts of all parties are extremely required in corruption eradication campaign. This article describes participation of Muhammadiyah in the campaign through religious discourse on anti-corruption. Muhammadiyah understands corruption not as mere theft, it is more than that.  The consequence of corruption is so harmful that Muhammadiyah attempt to locate corruption in the discourse of Islamic jurisprudence. It can be considered qulu’, rishwah or bribery, and other kinds of crime. Muhammadiyah also designs steps of corruption eradication from their Islamic perspective.